Epilepsy risk in offspring of affected parents; a cohort study of the "maternal effect" in epilepsy. Issue 1 (29th November 2020) - Dreier, Julie W.; Ellis, Colin A.; Berkovic, Samuel F.; Cotsapas, Chris; Ottman, Ruth; Christensen, Jakob
Abstract: Objective: To assess whether the risk of epilepsy is higher in offspring of mothers with epilepsy than in offspring of fathers with epilepsy. Methods: In a prospective population‐based register study, we considered all singletons born in Denmark between 1981 and 2016 ( N  = 1, 754, 742). From the Danish National Patient Register since 1977, we identified epilepsy diagnoses in all study participants and their family members. Cox regression models were used to estimate hazard ratios (HRs) and corresponding 95% confidence intervals (CI), adjusted for relevant confounders. Results: We included 1, 754, 742 individuals contributing > 30 million person‐years of follow‐up. The incidence rate of epilepsy in offspring of unaffected parents was 78.8 (95% CI: 77.8–79.8) per 100, 000 person‐years, while the corresponding rate in offspring with an affected father was 172 per 100, 000 person‐years (95% CI: 156–187) and in offspring with an affected mother was 260 per 100, 000 person‐years (95% CI: 243–277). Having an affected mother was associated with a 1.45‐fold (95% CI: 1.30–1.63) higher risk of epilepsy in the offspring, compared to having an affected father. This maternal effect was found both in male (HR = 1.39, 95% CI: 1.19–1.62) and female offspring (HR = 1.53, 95% CI: 1.30–1.80), and across various ages at onset in the offspring. The maternal effect was also found in familial epilepsies (i.e. where the affected parent had an affected sibling; HR = 1.50, 95% CI: 1.04−2.16). Interpretation: We found a clear maternal effect on offspring risk of epilepsy in this nationwide cohort study.